Magnetic resonance angiography for cerebral arterial and venous visualization in dogs: a comparative study of time-of-flight, phase-contrast, and time-resolved imaging of contrast kinetics sequences - Hong, Sunghwa; Kim, Soyeon; Namgoong, Mire; Kwon, Minjoo; Yoon, Junghee; Choi, Jihye (Frontiers in Veterinary Science, 2025)
This study aims to compare the effectiveness of three magnetic resonance angiography (MRA) sequences—Time-of-Flight (TOF), Phase-Contrast (PC), and Time-Resolved Imaging of Contrast Kinetics (TRICKS)—in visualizing cerebral arteries and veins in dogs. The goal is to determine the most suitable MRA sequence for improving diagnostic accuracy in canine cerebral imaging. Five healthy adult beagles underwent imaging using a 1.5-T MRI system. Quantitative measures, including signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR), were calculated, and qualitative evaluations of vessel delineation and visualization symmetry were performed by blinded observers. The three sequences were statistically compared using Friedman and Wilcoxon signed-rank tests. All dogs completed the imaging protocols without any complications. TOF MRA showed the best results for visualizing cerebral arteries, with the highest SNR and CNR in major arteries like the basilar, rostral, caudal cerebral, and caudal communicating arteries. TRICKS MRA performed better than TOF and PC for venous imaging, achieving higher SNR or CNR in most veins, including the transverse, temporal, straight sinus and dorsal cerebral vein, and had the shortest acquisition time. In qualitative evaluations, TOF MRA demonstrated acceptable or higher vascular visibility in most of brain arteries. All venous structures were significantly better visualized with TRICKS MRA compared to TOF MRA. Interobserver agreement was high, showing consistency in the results. These findings suggest that TOF is best for artery imaging, while TRICKS is ideal for venous imaging and faster procedures. TOF is recommended for clear and detailed imaging of cerebral arteries, while TRICKS is more suitable for imaging veins and situations where faster scans are needed. These results provide a basis for improving MRA techniques in veterinary medicine, helping to make diagnoses more accurate and procedures more efficient in both clinical practice and research.